The teaching of the philosophy of science in Perú today - PAZ Y MIÑO CONDE, MANUEL ABRAHAM (2019)
In this article we will mention: a) the courses of Epistemology, Philosophy of Science (and Technology), Theory of Science and Introduction to Science that are taught in various Peruvian universities both public and private at the pre and post-graduate level ; b) the books published, in the country, on the subject by university professors; c) various academic events on the subject organized in the universities; and d) some issues of journals dedicated to the philosophy of science.